(untitled) (The Shivapuri Journal, 2026)
The composition of security forces in multiethnic states has significant implications for national security, institutional cohesion, and societal stability. This article examines the relationship between the ethnic composition of security forces and national security through a qualitative and comparative analysis of global and South Asian case studies with particular reference to Nepal. The study adopts a comparative and analytical approach, focusing on ethnicity as an institutional factor shaping professionalism, cohesion, and effectiveness of security organizations. The article begins by establishing a conceptual framework that defines key terms and outlines the relevance of ethnic composition to national security. It then explores the theoretical linkages between ethnic representation, institutional harmony, and security outcomes. Selected global experiences from the ethnic composition in the Balkans, Africa, and Asia are analyzed to highlight both successful integration models and cases where ethnic divisions within security forces have contributed to internal friction and security challenges, followed by South Asian experiences. Against this broader comparative background, the article assesses Nepal’s experience. The article argues that Nepal’s security forces, particularly the Nepali Army, have historically functioned as a cohesive and inclusive institution, reflecting the country’s social diversity. Since its inception, the Nepali Army has served as a melting pot of various ethnic, caste, and regional groups, maintaining harmony and institutional integrity even during periods of political and security transition. A distinctive feature contributing to this is the barracks-based system, which promotes close interaction, shared identity, and discipline, thereby reinforcing cohesion and professionalism. The article concludes by highlighting that Nepal’s experience offers valuable insights into managing diversity within security forces and demonstrates how institutional cohesion and inclusiveness can strengthen national security. While challenges remain, Nepal’s case provides a meaningful reference for broader comparative discussions on security forces and national stability.